(untitled) (Bangladesh Journal of Botany, 2019)
Thirty two genotypes of Nigella sativa L. were evaluated for three consecutive years which showed significant differences for all the traits indicating high level of genetic variation. Heritability in broad sense ranged from 0.28 to 0.98 and the highest heritability was calculated for days to maturity and days to flowers. Grain yield was positively associated with plant height, capsule weight, capsule length, root length, whereas negatively with capsule width and 1000-seed weight that required the use of novel breeding techniques to break this undesired linkage to improve grain yield in N. sativa. Path coefficient indicated that direct effects of all the traits were positive except days to first flower, days to 50% flowers, flowering duration, number of capsules, root weight and harvest index. The characters exhibiting correlation along with direct effect towards grain yield viz., days to maturity, capsule weight, capsule length and root length should be given more preference while selecting high yielding N. sativa genotypes for future crop improvement programs.